Dark storm - Harper, Karen (Karen S.) (Harper, Karen (Karen S.) South Shores., 2019)
Forensic psychologist Claire Markwood has experienced her share of disaster. But nothing could prepare her for her sister, Darcy, going missing. Claire rushes to the butterfly sanctuary where Darcy has been working, prepared to do what she does best<U+2014>work the clues. But her sister, along with her car and some of the sanctuary<U+2019>s rarest species of butterflies, has seemingly vanished without a trace. Amid a flurry of mysterious leads and dead ends, Claire and her criminal lawyer husband, Nick, tap every resource at their disposal. But the deeper they dig, the more unsettling the case becomes, dredging up old family secrets that shake the foundation of everything Claire thought to be true. Because some secrets aren<U+2019>t just threatening<U+2014>they<U+2019>re deadly.